2023
DOI: 10.3390/jtaer18010019
|View full text |Cite
|
Sign up to set email alerts
|

Did New Retail Enhance Enterprise Competition during the COVID-19 Pandemic? An Empirical Analysis of Operating Efficiency

Abstract: The question concerning how digital consumption demand has been adapted and how matching business models have been built has become an important practical problem in the digital development of the retail industry. Considering the effects of COVID-19, whether new retail enterprises can maintain adequate competitiveness and risk resilience in the post-pandemic era deserves in-depth study. In comparing the development of traditional retail and new retail enterprises, we extracted and evaluated key factors of ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…These factors may vary depending on the product category, customer segment, and geographic location. Therefore, it is hard to predict how consumers' preferences will change after the pandemic [28]. However, some surveys suggest that online shopping will remain popular for certain categories such as groceries, household supplies, personal care products, and electronics [24,27], while physical shopping will regain some ground for categories such as clothing, footwear, jewelry and cosmetics [25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors may vary depending on the product category, customer segment, and geographic location. Therefore, it is hard to predict how consumers' preferences will change after the pandemic [28]. However, some surveys suggest that online shopping will remain popular for certain categories such as groceries, household supplies, personal care products, and electronics [24,27], while physical shopping will regain some ground for categories such as clothing, footwear, jewelry and cosmetics [25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of expectation on quality and satisfaction has also been examined empirically in the context of exchange programs. Student expectations in exchange programs may encompass personal experiences (Nilsson, 2015), communication skill improvement, learning about foreign cultures, and making new friends among local university students (Costas and Singco, 2016;Yang et al, 2023), community involvement attitudes, future professional work, personal reflection (Pereira et al, 2017), social, and academic development, improvement of foreign language skills (K€ uc x€ ukc xene & Akbasli, 2021), transfer of theoretical knowledge to practice, and a supportive learning environment (Dursun Ergezen et al, 2022). These studies have concluded that there is a positive correlation between expectation and satisfaction, as well as expectation and quality.…”
Section: Expectation Service Quality and Satisfaction In Higher Educa...mentioning
confidence: 99%
“…According to this model, customer satisfaction is a result of comparing their expectations with their actual experiences. However, measuring customer expectations can be complex and unreliable, and even if accurately measured, its impact on satisfaction formation may be minimal (Kristensen et al, 1999; Y. Yang et al, 2023).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…However, in the face of escalating environmental problems, effectively enhancing the export technological complexity of high-tech industries in China's manufacturing sector requires compliance with environmental regulatory requirements (Oginni and Omojowo 2016;Phuoc 2022;Yang et al 2023b). To further promote the development of China's manufacturing industry and the entire national economy, it is essential to study the impact of environmental regulations on the export technological complexity of high-tech industries.…”
Section: Introductionmentioning
confidence: 99%